Pendidikan Kewarganegaraan dan Keterampilan Berpikir - Montessori, Maria (Jurnal Demokrasi, 2002)
The aim of Civic Education is to prepare students to be effective and responsible citizens. Implicit in that aim is the need to help students to become more competent as thinkers. This article tries to address the important of moving from lower-order thinking to higher order thinking in civic education program. Three kinds of thinking, that is critical thinking, problem solving and decision making are reviewed in this article and assumed by the writer as important feature for achieving the aim of civic education. Â  Key Words: Civic education goals, thinking skills, lower-order thinking, higher-order thinking, critical thinking, problem solving, and decision making